Роль індексу згасання еходенситометрії у діагностиці неалкогольного стеатогепатозу хворих на цукровий діабет 2-го типу - Кобиляк, Н. М.; Боднар, П. М.; Динник, О. Б.; Михальчишин, Г. П. (Clinical Endocrinology and Endocrine Surgery, 2012)
In this article we give evaluation of diagnostic efficiency attenuation index in patients with type 2 diabetes with nonalcoholic steatosis. We noted higher efficiency for attenuation index in comparison with routine ultrasound examination of liver which is based on a qualitative assessment of fatty liver. Sensitivity and specificity for attenuation index in diagnosis of fatty liver with accumulation of over 30% was more than 90%.